The entrepreneur's investor choice: The impact on later-stage firm development - Schwienbacher, Armin (Journal of Business Venturing, 2013)
This article analyzes how early-stage financing decisions may affect how entrepreneurial firms ultimately grow. This theoretical study considers an entrepreneur seeking early-stage financing from either a specialist or a generalist investor in the context of stage financing. It is assumed that an early-stage specialist is less efficient in assisting a venture beyond the early-stage round than a generalist. This leads to the following tradeoff: by initially selecting an early-stage specialist, the entrepreneur benefits from increased investor incentives in the first round. Such incentives generate additional value for the entrepreneurial venture, improving valuation in the interim round and thereby mitigating the risk of dilution against follow-up investors and potentially even of premature discontinuation of the project. However, early-stage specialists are more reluctant to finance later rounds. Conversely, using a generalist secures efficient follow-up funding but also leads to weaker investor incentives in the early stage. With this tradeoff, the presence of asymmetric information about the quality of entrepreneurial projects particularly affects generalists; entrepreneurs with strong projects more often choose specialists, while entrepreneurs with weak projects select generalists to secure efficient continuation. The use of convertible securities or adjustment warrants in contracts cannot always eliminate the effect of asymmetric information. Several empirical implications derived from this tradeoff are provided for optimal investor choice.